2017
DOI: 10.17221/105/2017-pse
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic and selenium levels in rice fields from south-west of Spain: influence of the years of monoculture

Abstract: Rodrigo S., Santamaria O., Perez-Izquierdo L., Poblaciones M.J. (2017): Arsenic and selenium levels in rice fields from south-west of Spain: influence of the years of monoculture. Plant Soil Environ., 63: 184-188.There is a lack of information regarding the arsenic (As) and selenium (Se) concentrations in Spanish rice (Oryza sativa L.) fields and how soil conditions affect such concentration, especially those derived from the typical monoculture practiced in the studied area. To clarify these aspects, 76 soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The intensive cultivation of frequent irrigation requiring crops like low land rice turned out one of the major factors responsible for the deposition of seleniferous material in the soil, leaving more than 100 ha area under selenium toxicity (Dhillon and Dhillon 1991). Sara et al (2017) observed that arsenic and selenium content of soil increased with duration of rice monoculture system. The increase in arsenic and selenium concentration in soil caused toxicity in rice grain.…”
Section: Soil and Grain Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…The intensive cultivation of frequent irrigation requiring crops like low land rice turned out one of the major factors responsible for the deposition of seleniferous material in the soil, leaving more than 100 ha area under selenium toxicity (Dhillon and Dhillon 1991). Sara et al (2017) observed that arsenic and selenium content of soil increased with duration of rice monoculture system. The increase in arsenic and selenium concentration in soil caused toxicity in rice grain.…”
Section: Soil and Grain Toxicitymentioning
confidence: 99%
“…Needless to say that intensive rice cultivation with puddling and flooding method projects the health risk associated with soil and grain toxicity in long-term. Sara et al (2017) recommended to control these elements with prior importance by employing the different actions including crop rotations, soil amendments, etc.…”
Section: Soil and Grain Toxicitymentioning
confidence: 99%
“…Selenium (Se) is another essential micronutrient that accumulates in rice in a lower concentration than in other staple crops, with negative health impacts on an estimated one billion people globally (Combs Jr 2001, also cited by Carey et al 2012;Boldrin et al 2013). Selenium concentration in brown rice in Spain was found to be closely associated with total and available Se in the soil (Rodrigo et al 2017). Unlike Zn, the Se in rice was more responsive to soil application than foliar Se (Boldrin et al 2013).…”
Section: Nutritional Quality For Human and Crop Healthmentioning
confidence: 99%
“…The determination of Se in rice has been the object of a number of valuable analytical methods based on different instrumental approaches: among others, it is worthy to cite the voltammetry [50,51], the HR-CS AAS (high resolution continuous source atomic absorption spectroscopy) [52], the ICP-OES (inductively coupled plasma-optical emission spectroscopy) [53], and the INAA (instrumental neutron activation analysis) [54]. Also ICP-MS (inductively coupled plasma-mass spectrometry) methods have been often used for this aim [33,[55][56][57][58][59][60][61][62][63] but-unfortunately-their overall reliability is not proven because these methods were often not fully validated.…”
Section: Introductionmentioning
confidence: 99%